Does Satisfaction Increase Patient Loyalty? (Investigation on Jogja International Hospital Surakarta, Indonesia) - Sudarwati Sudarwati; Ida Aryati Diyah Purnomo Wulan; Adina Safitri Ayu Saputri (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to test and analyze the influence of patient satisfaction on patient loyalty. It also measures the role of consumer satisfaction as a mediating variable of brand trust and service quality on patient loyalty. This research used a quantitative descriptive approach. This research was conducted at JIH Solo Hospital, with 125 respondents. Sampling was done using the purposive sampling technique. This research was analyzed using Partial Least Square (PLS) with SmartPLS3 software. The research results showed that brand trust positively and significantly affected patient satisfaction. Service quality had a positive and significant impact on patient satisfaction. Brand trust had a positive and significant effect on patient loyalty. Service quality had a positive and significant impact on patient loyalty. Patient satisfaction had a positive and significant impact on loyalty. Patient satisfaction was a partial mediator of the influence of brand trust on patient loyalty. Patient satisfaction partially mediated the influence of service quality on patient loyalty.